2022
DOI: 10.1007/s11136-022-03253-5
|View full text |Cite
|
Sign up to set email alerts
|

Time trade-off health state utility values for depression: a systematic review and meta-analysis

Abstract: Purpose This study aims to systematically review the literature on health utility in depression generated by time trade-off (TTO) method and to compare health state vignettes. Methods Systematic literature search was conducted following PRISMA guideline in 2020 November (updated in 2022 March) in Pubmed, Web of Science, PsycInfo, and Cochrane Database of Systematic Reviews. Random effect meta-analysis was conducted to pool vignette-based utility values of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 72 publications
0
5
0
Order By: Relevance
“…This finding is in line with the previous studies. For example, a most recent survey on HSUs of depression reported that the pooled mean utilities of different depression-related health states ranged from 0.240 to 0.890 while mean utility values for mild, moderate and severe depression were 0.750, 0.660 and 0.500, respectively [ 103 ]. Another study also found that a less severe health state of depression was associated with high utility scores [ 104 ].…”
Section: Discussionmentioning
confidence: 99%
“…This finding is in line with the previous studies. For example, a most recent survey on HSUs of depression reported that the pooled mean utilities of different depression-related health states ranged from 0.240 to 0.890 while mean utility values for mild, moderate and severe depression were 0.750, 0.660 and 0.500, respectively [ 103 ]. Another study also found that a less severe health state of depression was associated with high utility scores [ 104 ].…”
Section: Discussionmentioning
confidence: 99%
“…Overall In total, 14 articles met the inclusion criteria, but two publications were merged, while reporting the results of the same study [106]. An additional empirical TTO study was found by hand searching the reference lists of included articles, resulting in 14 included individual studies…”
Section: Results Of Systematic Review In Depressionmentioning
confidence: 99%
“…previously published two articles [105,106] and two handed-in manuscripts [107,108] are presented. As main author (Péter Balázs) in the four publications, several parts of the studies were used in this thesis.…”
Section: Note: the Following Four Chapters (4-7) Present The Methods ...mentioning
confidence: 99%
See 2 more Smart Citations